Modelling of surface roughness for glass-assisted co2 laser machined p-type silicon wafer - Sivarao, Subramonian; Prasath, K.P.; Ramesh, S.; Kadirgama, Kumaran; Pujari, S.; Vatesh, Umesh Kumar; Salleh, Mohd Shukor; Ali, Mohd Amran; Maidin, Shajahan (2023)
Carbon Dioxide (CO2) Laser Machining has been in high demand as compared to other high-end conventional machining processes as it is capable of producing super precision cutting with a non-contact technology. The objective of this research is to establish mathematical model to predict laser cut surface roughness of the P-type silicon wafer processed with assistive Pyrex glass. The design parameters employed in this fractional factorial design of experiment were laser power, cutting speed, and pulse frequency. P-type silicon wafers were machined using assistive Pyrex glass to observe if it gives significant effect on the cut quality. Commercially available statistical package namely Response Surface Methodology (RSM) was used to optimise the design parameters and establish the predictive model. The findings reveal that, Pyrex glass assisted laser machining has significant contribution in the laser processing of P-type silicon wafer.